Investigating cryptocurrencies : understanding, extracting, and analyzing blockchain evidence - Furneaux, Nick (Wiley, 2018)
"Bitcoin has traditionally been the payment system of choice for a criminal trading on the Dark Web, and now many other blockchain cryptocurrencies are entering the mainstream as traders are accepting them from low-end investors putting their money into the market. Worse still, the blockchain can even be used to hide information and covert messaging, unknown to most investigators. Investigating Cryptocurrencies is the first book to help corporate, law enforcement, and other investigators understand the technical concepts and the techniques for investigating crimes utilizing the blockchain and related digital currencies such as Bitcoin and Ethereum."--